2011
DOI: 10.1901/jaba.2011.44-375
|View full text |Cite
|
Sign up to set email alerts
|

Using Noncontingent Reinforcement to Increase Compliance With Wearing Prescription Prostheses

Abstract: We evaluated the effects of noncontingent reinforcement (NCR) on compliance with wearing foot orthotics and a hearing aid with 2 individuals. Results showed that NCR increased the participants' compliance with wearing prescription prostheses to 100% after just a few 5-min sessions, and the behavior change was maintained during lengthier sessions. The results are discussed in terms of the potential value-altering effects of NCR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
17
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 6 publications
(7 reference statements)
1
17
0
2
Order By: Relevance
“…Escape. This condition was similar to the escape baseline condition that has been used in previous studies of passive compliance (e.g., DeLeon et al, 2008;Richling et al, 2011). Each trial began when a therapist said, "Jonah, it's time to wear your bracelet now," and then placed the bracelet on Jonah's wrist; this process required 2 to 4 s. Contingent on Jonah's engagement in problem behavior, the therapist removed the bracelet for 30 s and ended the trial.…”
Section: Design and Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…Escape. This condition was similar to the escape baseline condition that has been used in previous studies of passive compliance (e.g., DeLeon et al, 2008;Richling et al, 2011). Each trial began when a therapist said, "Jonah, it's time to wear your bracelet now," and then placed the bracelet on Jonah's wrist; this process required 2 to 4 s. Contingent on Jonah's engagement in problem behavior, the therapist removed the bracelet for 30 s and ended the trial.…”
Section: Design and Proceduresmentioning
confidence: 99%
“…Compliance can be subcategorized as being active or passive; the former requires an individual to emit a specific response, whereas the latter does not (Neil, 2011). Passive compliance may involve teaching an individual to sit still, abstain from engaging in specific behavior, or otherwise tolerate an unpleasant event or stimulus.…”
mentioning
confidence: 99%
“…Children with autism and other developmental disabilities may display noncompliant or avoidant behavior in the presence of specific stimuli or events. Such problem behavior may decrease the individual's compliance with prescribed dental or medical procedures (e.g., Altabet, 2002; Cuvo, Reagan, Ackerlund, Huckfelddt, & Kelly, 2010; Richling, Rapp, Carroll, Smith, Nystedt, & Siewert, in press; Shabani & Fisher, 2006), increase aberrant behaviors in public places (e.g., Ricciardi, Luiselli, & Camare, 2006), or both. A variety of behavioral interventions have been used to increase individuals' proximity to or tolerance of an avoided stimulus or event.…”
Section: Introductionmentioning
confidence: 99%
“…Their results indicated that NCR alone increased compliance with one participant, whereas the addition of response blocking and response cost were necessary for the remaining participants. In a replication and extension, Richling et al () found that NCR alone increased compliance with wearing foot orthopedics and hearing aids in two children with developmental disabilities. More recently, Cook et al () reported that differential negative reinforcement of other behavior (DNRO) increased compliance with wearing a medical bracelet in one child with autism.…”
mentioning
confidence: 99%
“…Researchers have shown that behavioral interventions are effective at increasing compliance with wearing medical devices in children with developmental disabilities (Cook, Rapp, & Schulze, ; DeLeon et al, ; Richling et al, ). For example, DeLeon et al () implemented noncontingent reinforcement (NCR) to increase the wearing of prescription glasses in four participants with intellectual disabilities.…”
mentioning
confidence: 99%